Charter and Ordinances of the City of Olympia: Also General Laws of Washington Territory, Relative to the Government of Incorporated Cities and Towns, at 90, Ordinance No. 241, § 1 (1886) - (:unkn) unknown (General Publisher, 1886)
Any person or persons who shall store any gunpowder, giantpowder, dynamite or nitro-glycerine, in any combustible form, within the fire limits of the City of Olympia, or in any building or place within three hundred yards of the dwelling house or building of another within the City of Olympia, shall be deemed guilty of a misdemeanor, and upon conviction thereof shall be fined in any sum not greater than one hundred dollars nor less than twenty-five dollars. Provided, That any person may keep gunpowder in any quantity not to exceed fifty pounds at any one time, within such limits or places for private use or sale.
--
Keywords: GUN POWDER STORAGE